Hypoxia inducible factor-1α correlates with vascular endothelial growth factor A and C indicating worse prognosis in clear cell renal cell carcinoma - Grahovac Blaženka; Grahovac Maja; Hadžisejdić Ita; Babarović Emina; Matušan-Ilijaš Koviljka; Đorđević Gordana; Jonjić Nives (Journal of Experimental & Clinical Cancer Research, 2009)
Abstract Background The role of angiogenesis in the pathogenesis of renal cell carcinoma is well recognized, however, the influence of tumor cells in this activity has not yet been fully clarified. The aim of this study was to analyze the expression of hypoxia inducible factor-1α (HIF-1α), a regulatory factor of angiogenic switch, in comparison to vascular endothelial growth factor A and C (VEGF-A and VEGF-C), recognized to be involved in blood and lymph vessel neoangiogenesis, with potential association in the prognosis of patients with renal cell carcinoma. Methods Ninety-four patients with diagnosis of clear cell renal cell carcinomas (CCRCC), all clinicopathological characteristics and overall survival were unrolled in this study. Immunohistochemicaly VEGF-A, VEGF-C, HIF-1α and Ki67 were detected on tumor cells and the staining was performed on tissue microarrays (TMA). The staining was evaluated as a percentage of cytoplasmic or nuclear positive tumor cells. Results Variable expression of all three proteins was confirmed. Both angiogenic factors demonstrated perimembranous or diffuse cytoplasmic staining, with diffuse pattern positively associated (p < 0.001). Nuclear HIF-1α expression (nHIF-1α) showed inverse correlation with diffuse cytoplasmic VEGF-A (p = 0.002) and VEGF-C (p = 0.053), while cytoplasmic HIF-1α expression (cHIF-1α) showed positive correlation with diffuse staining of both angiogenic factors (p < 0.001; p < 0.001, respectively). In comparison to clinicopathological characteristics, a higher nuclear grade (p = 0.006; p < 0.001, respectively), larger tumor size (p = 0.009; p = 0.015, respectively), higher stage (p = 0.023; p = 0.027, respectively) and shorter survival (p = 0.018; p = 0.024, respectively) were associated with overexpression of cHIF-1α and diffuse cytoplasmic VEGF-A expression. In contrary, overexpression of nHIF-1α was associated with better diagnostic parameters i.e. lower nuclear grade (p = 0.006), smaller tumor size (p = 0.057), and longer survival (p = 0.005). Conclusion Overexpression of VEGF-A and cHIF-1α in tumor cells highlights a more aggressive subtype of CCRCC that might have some clinical implications. The significance of nHIF-1α expression associated with better differentiated tumors should be further elucidated.